2021
DOI: 10.1080/13563467.2021.1910648
|View full text |Cite
|
Sign up to set email alerts
|

The Eurozone’s Evolving Fiscal Ecosystem: Mitigating Fiscal Discipline by Governing Through Off-Balance-Sheet Fiscal Agencies

Abstract: The original Maastricht regime designed the Eurozone's fiscal segment in a way that sought to keep member states' treasury budgets balanced by disciplining them through market forces, reducing the overall volume of public indebtedness, prohibiting monetary financing, and avoiding that Eurozone treasuries bail each other out. In this article, we analyse how these 'neoliberal' rules for fiscal governance have been gradually superseded by an alternative approach that we call 'governing through off-balance-sheet f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 50 publications
(41 reference statements)
0
24
0
Order By: Relevance
“…Changes in the external macroeconomic environment, the rising politicisation of European integration (Schmidt 2019 ), shifting economic policy debates inside the Eurozone (Schmidt 2016 ; Vanheuverzwijn and Crespy 2018 ; Crespy and Vanheuverzwijn 2019 ; Miró 2021 ; Guter-Sandu and Murau 2021 ), the arrival of new leadership at the helm of the ECB, and the ideational entrepreneurship of ECB staff, these were pivotal factors that enabled the emergence of new economic policy ideas inside the ECB. In particular, I contend that a key driver of ECB ideational change was the shift of power relations among ideational constituencies inside the ECB.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the external macroeconomic environment, the rising politicisation of European integration (Schmidt 2019 ), shifting economic policy debates inside the Eurozone (Schmidt 2016 ; Vanheuverzwijn and Crespy 2018 ; Crespy and Vanheuverzwijn 2019 ; Miró 2021 ; Guter-Sandu and Murau 2021 ), the arrival of new leadership at the helm of the ECB, and the ideational entrepreneurship of ECB staff, these were pivotal factors that enabled the emergence of new economic policy ideas inside the ECB. In particular, I contend that a key driver of ECB ideational change was the shift of power relations among ideational constituencies inside the ECB.…”
Section: Discussionmentioning
confidence: 99%
“…And so, the state can cut spending, and even tackle inflation, by increasing the amount of work women are doing, without increasing their income. By moving a care responsibility from paid to unpaid, states are essentially performing a gendered sort of balance-sheet management, not dissimilar to more recent attempts to move state spending off balance sheet onto private or semi-private institutions (Guter-Sandu and Murau 2022 ). Moreover, such a re-privatisation of care responsibilities is not matched by increases in time for women or others to perform such care work—so they are unpaid and un-resourced in terms of time.…”
Section: The Deflationary Biasmentioning
confidence: 99%
“…Discussions regarding public finances comprise issues such as the reform of public finances [5][6][7], quality of public financial management [8], and public finance sustainability [10]. Studies have reported that less developed economies are more exposed to the risks of short-term budgetary deficits [27].…”
Section: Sustainability Of Public Financesmentioning
confidence: 99%
“…Public finances play an important role in ensuring social progress. The literature reports such developments on the subject as the focus on the quality of public finance [2][3][4], public finance reform [5][6][7], the quality of public financial management [8,9], and the sustainability of public finances [10][11][12].…”
Section: Introductionmentioning
confidence: 99%